Participants Satisfaction Towards the Basic Training of Civil Servant Candidates Group II Batch III Bangka Belitung Province in 2022 - Gunawan, Gunawan (Scientia: Jurnal Hasil Penelitian, 2022)
This research aims to determine the satisfaction of participants the basic training for civil servants candidates of group II batch III Bangka Belitung Province toward the learning realisation. A quantitative approach uses in this study with a survey method to figured out the factors of satisfaction of participants. In this research, questionnaire uses as an instrument to collect the data from the participants. The questionnaire is assessed into 5 category quality of service which are tangible, reliability, responsiveness, assurance and empathy. As for the results from the 5 category, all showed very satisfying. The score of each category of responsiveness, assurance, and empathy is 4.70, reliability with score 4,65, tangible with score 4,58. Overall, the learning realisation of the basic training for civil servants candidates of group II batch III of the Bangka Belitung Province in 2022 were satisfying for the participants with an average score of 4.68.